Ascarophisnema hoiae n. sp. (Nematoda: Cystidicolidae), from the stomach of the trumpeter whiting, Sillago maculata Quoy & Gaimard (Perciformes: Sillaginidae) from Moreton Bay, Queensland, Australia - Beveridge, Ian; Moravec, František (Systematic parasitology, 2020)
Ascarophisnema hoiae n. sp. (Nematoda: Cystidicolidae) is described from the stomach of the trumpeter whiting, Sillago maculata Quoy & Gaimard (Perciformes: Sillaginidae) from Moreton Bay, Queensland, Australia. It differs morphologically from the only other valid congener, A. tridentatum Moravec & Justine, 2010 in the shape of the sub-labium and in the lengths of the spicules and the morphology of their distal tips (bifid). It represents the first record of this genus from Australia and appears to be highly oioxenous, having been found only in this host species among 133 other species of fish examined at the same locality.
Keywords: Queensland; Bays; Spiruroidea; Perciformes; druhová specificita; zvířata; zátoky; Species Specificity; Animals